Aspectos psicossociais e capacidade para o trabalho nos trabalhadores da saúde no contexto da Pandemia de COVID-19: estudo longitudinal - Martinez, Carolina Luciane Nogueira (2024)
Psychosocial factors at work result from the interaction between the work environment and human factors, such as capabilities and expectations, and can influence health, performance and work ability. The COVID-19 pandemic has led to changes in the working conditions of healthcare professionals (HCPs), and it is necessary to monitor the effects of the pandemic on psychosocial factors and work ability in this population. Objective: To assess psychosocial factors and work ability of healthcare workers during the COVID-19 pandemic. Methods: This is a longitudinal study with a prospective follow-up of 36 months. A total of 1,211 workers participated in the baseline assessment in 2020, including 219 healthcare professionals (HCPs) and 992 non-healthcare professionals (NHCPs). Participants answered a sociodemographic questionnaire, the short version of the Copenhagen Psychosocial Questionnaire (COPSOQ II-Br), and the Work Ability Index (WAI) at four time points: baseline, 12, 24, and 36 months after the baseline assessment. COPSOQ II-Br covers seven domains: work demands, organization and content, interpersonal relationships, work-individual interface, values in the workplace, health and well-being and offensive behaviors, composed of questions divided into eleven dimensions that measure exposure indicators (risks). The final version of COPSOQ II-Br was formulated and cross-culturally adapted for the Brazilian population. Data were analyzed descriptively and using the Chi-square and Cochran’s tests for inter- and intra-group comparisons, respectively. Results: Emotional demands, influence at work, predictability, general health, burnout, unwanted sexual attention, threat of violence, and violence were psychosocial factors of concern among HCPs. The possibility of development, meaning of work, commitment to work and role clarity were favorable factors in HCPs. Work ability was good in both groups and moments investigated. Conclusions: HCPs were exposed to some psychosocial risk factors that are unfavorable to their health and well-being, which deserve attention. The persistence of work risk factors demonstrates the need for long-term measures for worker health after emergency situations.